ASSESSMENT OF SOCIAL CAPITAL INFLUENCE ON ECONOMICS OF ENTERPRISES - Z. Mamsurova (Вестник университета)
The article describes the results of research of the social capital and its influence on economic results of activity of the enterprises. The analysis of approaches to the concept «social capital» is carried out, its components are defined, a number of regularities of its impact on economic indicators of the enterprises is revealed.